Industry 4.0 and Business Policy Development: Strategic Imperatives for SME Performance - Normala S Govindarajo; Dileep Kumar M; Erum Shaikh; Mukesh Kumar; Pramod Kumar (ETIKONOMI, 2021)
Industry 4.0 presents companies with new prospects to renovate industrial manufacturing processes and increase value creation, has promised several optimizing strategies for improved business performance. The purpose of this research is to examine the relationship between innovation capability and employee capability on organizational performance among Small and Medium Scale industries entrepreneurs. Following a positivist research philosophy with a quantitative, cross-sectional descriptive study design, the study addressed three direct and two indirect relationships in the model. The research followed the expectation Resource-Based View Theory to test the theoretical model. Following stratified random sampling, this research using 384 SME entrepreneurs from the Selangor state of Malaysia. The study applied Smart PLS-SEM to analyze the data. The results show that SME firms' innovation capability and employee capability positively correlate with business performance. The study also shows the partial mediation effect of technology change on innovation capability and business performance and employee capability and business performance. Research extends practical and theoretical implications to the stakeholders of SMEs and businesses.JEL Classification: L25, L26, L29How to Cite:Govindarajo, N. S., Kumar M, D., Shaikh, E., Kumar, M., & Kumar, P. (2021). Industry 4.0 and Business Policy Development: Strategic Imperatives for SME Performance. Etikonomi, 20(2), 213 – xx. https://doi.org/10.15408/etk.v20i2.20143.